Extension of the phenotypic spectrum of GLE1‐related disorders to a mild congenital form resembling congenital myopathy - Mathieu Cerino; Chloé Di Meglio; Francesca Albertini; Frédérique Audic; Florence Riccardi; Christophe Boulay; Nicole Philip; Marc Bartoli; Nicolas Lévy; Martin Krahn; Brigitte Chabrol (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background GLE1 (GLE1, RNA Export Mediator, OMIM#603371) variants are associated with severe autosomal recessive motor neuron diseases, that are lethal congenital contracture syndrome 1 (LCCS1, OMIM#253310) and congenital arthrogryposis with anterior horn cell disease (CAAHD, OMIM#611890). The clinical spectrum of GLE1‐related disorders has been expanding these past years, including with adult‐onset amyotrophic lateral sclerosis (ALS) GLE1‐related forms, especially through the new molecular diagnosis strategies associated with the emergence of next‐generation sequencing (NGS) technologies. However, despite this phenotypic variability, reported congenital or ALS adult‐onset forms remain severe, leading to premature death. Methods Through multidisciplinary interactions between our Neuropediatric and Medical Genetics departments, we were able to diagnose two siblings presenting with congenital disorder, using an NGS approach accordingly to the novel French national recommendations. Results Two siblings with very similar clinical features, meaning neuromuscular disorder of neonatal onset with progressive improvement, were examined in our Neuropediatrics department. The clinical presentation evoked initially congenital myopathy with autosomal recessive inheritance. However, additional symptoms such as mild dysmorphic features including high anterior hairline, downslanted palpebral fissures, anteverted nares, smooth philtrum with thin upper‐lip, narrow mouth and microretrognathia or delayed expressive language and postnatal growth retardation were suggestive of a more complex clinical presentation and molecular diagnosis. Our NGS approach revealed an unexpected molecular diagnosis for these two siblings, meaning the presence of the homozygous c.1808G>T GLE1 variant. Conclusions We here report the mildest phenotype ever described, in two siblings carrying the homozygous c.1808G>T GLE1 variant, further widening the clinical spectrum of GLE1‐related diseases. Moreover, by reflecting current medical practice, this case report confirms the importance of establishing regular multidisciplinary meetings, essential for discussing such difficult clinical presentations to finally enable molecular diagnosis, especially when NGS technologies are used.